2007
DOI: 10.1038/sj.leu.2404546
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1-induced T-cell leukemia in transgenic zebrafish

Abstract: Activating mutations in the NOTCH1 gene have been found in about 60% of patients with T-cell acute lymphoblastic leukemia (T-ALL). In order to study the molecular mechanisms by which altered Notch signaling induces leukemia, a zebrafish model of human NOTCH1-induced T-cell leukemia was generated. Seven of sixteen mosaic fish developed a T-cell lymphoproliferative disease at about 5 months. These neoplastic cells extensively invaded tissues throughout the fish and caused an aggressive and lethal leukemia when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 62 publications
4
94
0
Order By: Relevance
“…Overexpression of TEL-AML1 led to the development of infiltrating B-lineage leukemia while rag2-mediated Notch overexpression resulted in T-cell leukemia. Both cancers also displayed similar properties with respect to mammals (Sabaawy et al, 2006;Chen et al, 2007).…”
Section: Transgenic Linesmentioning
confidence: 68%
See 1 more Smart Citation
“…Overexpression of TEL-AML1 led to the development of infiltrating B-lineage leukemia while rag2-mediated Notch overexpression resulted in T-cell leukemia. Both cancers also displayed similar properties with respect to mammals (Sabaawy et al, 2006;Chen et al, 2007).…”
Section: Transgenic Linesmentioning
confidence: 68%
“…In a separate study, the same group showed that irradiation or dexamethasone-induced apoptosis of fish leukemic cells is dependent on bcl-2 gene function that also operates in mammalian forms of leukemia (Langenau et al, 2005b). Two independent studies used a similar approach to induce different subtypes of leukemia mediated by overexpression of the aberrant TEL-AML1 fusion protein using the ubiquitous b-actin promoter or overexpression of Notch using the rag2 promoter (Sabaawy et al, 2006;Chen et al, 2007). Overexpression of TEL-AML1 led to the development of infiltrating B-lineage leukemia while rag2-mediated Notch overexpression resulted in T-cell leukemia.…”
Section: Transgenic Linesmentioning
confidence: 99%
“…47 Targeted expression of the active form of Notch 1 to immature T cells in a zebrafish transgenic model resulted in the development of T-cell leukemias. 48 The presence of Notch mutations are counterintuitively predictive of good initial therapeutic responses, although not of outcome. [49][50][51] Therapeutic strategies that combine inhibition of Notch processing by g-secretase inhibitors ( Figure 2) with glucocorticoids may be of value in the treatment of T-ALL.…”
Section: Transcriptional Targets Of P53mentioning
confidence: 99%
“…In another leukemia model, the knowledge was used that activating mutations in NOTCH1 are found in f60% of T-cell acute lymphoblastic leukemia. Zebrafish expressing constitutively active human NOTCH under the rag2 promotor developed T-cell leukemia at 5 to 11 months in f40% of the cases (39). When crossing these fish with the bcl2-overexpressing line (38), disease onset was accelerated and the leukemias were not radiation sensitive anymore, as apoptosis was inhibited.…”
Section: Transgenic Zebrafish Expressing Mammalian Oncogenesmentioning
confidence: 99%